An?lise argumentativa dos pronunciamentos do presidente do Brasil (2019-2022) em cadeia nacional - Guimar?es, Bruno de Azevedo Santana (2024)
Arguments are not universal and timeless. Arguments and their argumentative schemes are determined not by the speaker of the speech, but by the doxic current in which it is inscribed. In Brazil, the so-called Bolsonarist discourse became known for bringing together intolerant and hate speeches that had previously been dispersed, which justifies the conduct of research on the reproduction of arguments of intolerance and hate in the speech of the then president of the Republic, indicted in the Covid-19 CPI Report for 9 crimes committed by his government during the pandemic. Thus, we present our doctoral research, whose general objective is to analyze the arguments and argumentative schemes produced by the Brazilian president's nationally broadcast speeches during the pandemic period, in order to identify how these arguments and argumentative schemes function in the speech given by the president. Furthermore, from an analytical point of view, we contextualize each speech as a way of situating the historical period that Brazil and the world were facing and we show how arguments and argumentative schemes work in the construction of the speaker and the audience in relation to the beliefs and values shared between the subjects of the discourse. From a theoretical point of view, this research addresses the argumentative phenomena described by Perelman's New Rhetoric, assuming the point of view of commentators as proposed by Amossy (2020), Gr?cio (2021) e Toulmin (2008). The corpus is constituted from the presidential speeches made during the pandemic on national radio and television, whose texts and videos are available on the Portal of the Presidency of the Republic. In this work, we show how the presidential speech, in times of pandemic, has a direct impact on society from the fear spread by the coronavirus. Furthermore, the research contributes effectively to studies of argumentation and to reflection on the characteristics of hate speech and intolerance present in political discourse, especially when the political actor speaks from a position of power.